RADT-17. FOCUSED ULTRASOUND MEDIATED BLOOD–BRAIN BARRIER OPENING IS SAFE AND FEASIBLE CONCURRENT WITH AND ADJUVANT TO A CLINICAL RADIATION SCHEME FOR BRAINSTEM DMG. (12th November 2021) - Tazhibi, Masih; McQuillan, Nicholas; Wei, Hong-Jian; Pouliopoulos, Antonios; Bendau, Ethan; Englander, Zachary; Webster, Andrea; Yoh, Nina; Zacharoulis, Stergios; Konofagou, Elisa; Wu, Cheng-Chia
Abstract: Diffuse midline gliomas (DMG) are pediatric tumors with dismal prognosis. When these tumors emerge in the brainstem, there exists no feasible method of surgical resection or systemic intervention, making ionizing radiation the sole therapeutic avenue to date. However, radiotherapy (RT) provides only marginal survival benefit as the topographically diffuse and highly infiltrative tumors spread in areas in which the blood-brain barrier (BBB) is relatively intact. Focused ultrasound (FUS) with intravenous microbubbles provides a compelling solution, transiently and non-invasively opening the BBB to allow drug delivery across the cerebrovasculature. Nonetheless, it remains unclear whether FUS can be safely administered at the brainstem in patients receiving RT. Therefore, the goal of this study was to assess the safety and feasibility of FUS administered concurrent with and adjuvant to a clinical hypofractionated radiation scheme for brainstem DMG. Non-tumor bearing B6 albino mice were randomly assorted into control, RT, FUS, and RT+FUS groups. Mice designated RT+FUS received 39Gy/13fx (hypofractionated RT scheme) to the brainstem with two sessions of FUS approximately 1 week apart. A single-element, spherical-segment FUS transducer driven by a function generator through a power amplifier was used with concomitant microbubble injection to sonicate the brainstem. Magnetic resonance imaging (MRI) was used to confirm BBB opening and cardiopulmonary measures were recorded throughout sonication. Vitals were assessed daily, and all treatment animals underwent Kondziela inverted screen testing and sequential weight lifting to assess brainstem-related strength and motor coordination deficits. In both FUS and RT+FUS mice, MRI confirmed brainstem BBB opening and subsequent closure within 96 hours. Mouse weights were stable, with slight drops (mean=5.5%) following FUS that resolved within three days. No attenuation in cardiorespiratory, strength, and motor coordination measurements was observed from FUS. FUS is a safe and feasible technique for brainstem BBB opening concurrent with and adjuvant to clinical hypofractionated RT.